Policy Uncertainty, Official Social Capital, and the Effective Corporate Tax Rate—Evidence From Chinese Firms - Wang, Long; Yang, Dong; Luo, Dongdong (Frontiers in Psychology, 2022)
The political environment has a significant impact on the sustainable development of enterprises. This paper aims to investigate the effect of policy uncertainty and official social capital on enterprises’ effective tax rate (ETR) due to the change of officials. Based on the panel data from the Chinese Industrial Enterprise Database from 1998 to 2009, it is shown that the policy uncertainty caused by the change of local government officials significantly increases the ETR of enterprises. Meanwhile, municipal officials who have social ties with provincial officials in their province also tend to raise the ETR of industrial enterprises, and this tendency is more evident when the officials take office. Further research shows that the effects vary in many aspects for policy uncertainty and social capital on the ETR of enterprises. The findings of this paper provide support for a deeper understanding of the change in local government fiscal policies and give suggestions to strengthen political environmental governance for the sustainable development of enterprises.